2016
DOI: 10.3892/etm.2016.4011
|View full text |Cite
|
Sign up to set email alerts
|

Geniposide reverses multidrug resistance in vitro and in vivo by inhibiting the efflux function and expression of P-glycoprotein

Abstract: Geniposide is a water-soluble iridoid glucoside with anti-oxidant and anti-inflammatory biological functions. It has been indicated that geniposide may increase doxorubicin (DOX) accumulation in drug-resistant tumor cells. The present study aimed to investigate the resistance-reversing effect of geniposide in DOX-resistant cells and assess the underlying mechanisms of its action. The results revealed that geniposide itself weakly inhibited tumor cell growth. Furthermore, geniposide effectively reversed DOX res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…However, the response of breast cancer patients to ADR is very poor, with no significant increase in patient survival. Previously, numerous mechanisms of ADR resistance, especially the rate of drug influx or efflux, have been identified [26-28]. In this study, we demonstrate a novel mechanism of chemoresistance by which cancer cells increase glycolytic flux.…”
Section: Discussionmentioning
confidence: 69%
“…However, the response of breast cancer patients to ADR is very poor, with no significant increase in patient survival. Previously, numerous mechanisms of ADR resistance, especially the rate of drug influx or efflux, have been identified [26-28]. In this study, we demonstrate a novel mechanism of chemoresistance by which cancer cells increase glycolytic flux.…”
Section: Discussionmentioning
confidence: 69%
“…This compound has the IUPAC name methyl (1S,4aS,7aS)-7-(hydroxymethyl)-1-[3,4,5-trihydroxy-6-(hydroxymethyl)oxan-2-yl]oxy-1,4a,5,7a-tetrahydrocyclopenta[c]pyran-4-carboxylate and the common name geniposide and is one of the major iridoid glycosides of gardenia fruit. It was previously shown to inhibit 5-lipoxygenase [33] and the tumor-promoting factor P-glycoprotein [34] and have anti-angiogenic activity [35] and potential antiasthma properties [36]. Additionally, geniposide was shown recently to protect against sepsis-induced myocardial dysfunction by activating AMPKα to suppress myocardial reactive oxygen species (ROS) accumulation [37].…”
Section: Resultsmentioning
confidence: 99%
“…[ 14 ] It has been proved to play outstanding antitumor activities on human oral squamous carcinoma, osteosarcoma, and glioma through inhibiting cell proliferation and promoting cell apoptosis. [ 20‐22 ] Besides that, Galvez et al [ 49 ] indicated that geniposide was able to exert anticancer activity on other tumors such as renal adenocarcinoma, breast adenocarcinoma, and melanoma by stabilizing covalent attachment of the topoisomerase I subunits to DNA at sites of DNA strand breaks.…”
Section: Discussionmentioning
confidence: 99%
“…[ 19 ] For antitumor activity, Qian et al [ 20 ] indicated that geniposide could inhibit cell proliferation and induce cell apoptosis of human oral squamous carcinoma HSC‐3 cells. Huang et al [ 21 ] proved that geniposide could reverse multidrug resistance of tumor therapy in vivo and in vitro by suppressing the P‐glycoprotein activity. For central nervous system tumors, previous studies reported that geniposide could inhibit glioma C6 cell metastasis by suppressing matrix metalloproteinase‐2 (MMP‐2) expression and induce cell apoptosis by activating mitogen‐activated protein kinase (MAPK)‐mediated activator protein‐1 (AP‐1).…”
Section: Introductionmentioning
confidence: 99%